2022
DOI: 10.3389/fenvs.2022.889239
|View full text |Cite
|
Sign up to set email alerts
|

Economically optimizing elevation of new, single-family residences for flood mitigation via life-cycle benefit-cost analysis

Abstract: Construction with freeboard—vertical height of a structure above the minimum required—is commonly accepted as a sound investment for flood hazard mitigation. However, determining the optimal height of freeboard poses a major decision problem. This research introduces a life-cycle benefit-cost analysis (LCBCA) approach for optimizing freeboard height for a new, single-family residence, while incorporating uncertainty, and, in the case of insured homes, considering the costs from losses, insurance, and freeboard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The first Intergovernmental Panel on Climate Change (IPCC) report (Cutter et al, 2012) confirmed these assertions by reporting that societal exposure (and therefore risk as defined here) is a product of development processes on hazardous landscapes and also is an anticipated key driving force contributing to future vulnerability to extreme weather events (Pielke Sr et al, 2007;Hinkel et al, 2010). There remains a paucity of risk assessment work at a scale more local than countylevel, especially while also considering changing hazard intensities (Gnan et al, 2022a(Gnan et al, , 2022bMostafiz et al, 2022b, Mostafiz et al, 2022Rahim et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…The first Intergovernmental Panel on Climate Change (IPCC) report (Cutter et al, 2012) confirmed these assertions by reporting that societal exposure (and therefore risk as defined here) is a product of development processes on hazardous landscapes and also is an anticipated key driving force contributing to future vulnerability to extreme weather events (Pielke Sr et al, 2007;Hinkel et al, 2010). There remains a paucity of risk assessment work at a scale more local than countylevel, especially while also considering changing hazard intensities (Gnan et al, 2022a(Gnan et al, , 2022bMostafiz et al, 2022b, Mostafiz et al, 2022Rahim et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…The building AAL (𝐴𝐴𝐿 ) is estimated using the method presented in Gnan (2021) and Gnan et al (2022a). Flood depths derived from Monte Carlo simulations (e.g., Brodie, 2013;Hennequin et al, 2018;Kind, 2014;Kind et al, 2020;Qi et al, 2013;Rahim et al, 2021Rahim et al, , 2022aRahman et al, 2002;Taghinezhad et al, 2020;Yu et al, 2013) with the fitted Gumbel extreme value distribution (e.g., Al Assi et al, 2022;Bhat et al, 2019;Gnan et al, 2022b;Kim & Lee, 2021;Manfreda et al, 2021;Mostafiz et al, 2021a;2022b;Rahim et al, 2022b;Singh et al, 2018) are translated to building loss percentages using the U.S. Army Corps of Engineers (USACE; 2000) depth-damage function (DDF) designed for the home's attributes (e.g., onestory or two-or-more stories, with or without basement).…”
Section: Building Aalmentioning
confidence: 99%
“…The flood premium deductible for a building is represented within the flood loss, as the policyholder is liable for the specified deductible and loss above coverage while NFIP covers the remaining balance within coverage. Thus, the building AAL is apportioned as either landlord loss (𝐴𝐴𝐿 ) or NFIP loss (𝐴𝐴𝐿 ) using the methodology presented in Gnan (2021) and Gnan et al (2022a).…”
Section: Building Aalmentioning
confidence: 99%
See 2 more Smart Citations